Thrombophilia’s in Patients with Diabetes Mellitus - Umurzakova Rokhila Zokirovna. (Zien Journals, 2024)
A clinical case of severe manifestation of type 2 diabetes mellitus in a teenage boy with obesity and the development of severe ketoacidosis as part of multiple organ failure syndrome is described. Timely elimination of diabetic ketoacidosis, hemodialysis and complex therapy in a multidisciplinary hospital made it possible to improve the teenager’s condition and avoid death.
Keywords: diabetes mellitus type 2; method; treatment; obesity